Financial inclusion in Peru and Latin America in times of COVID-19 - Vargas García, Allan Herminio (2021)
This study analyzes the consequences of COVID-19 in Peru and Latin America regarding the aspects of poverty and unemployment, the impact on the economic-social scenarios, and the existing financial inclusion indicators in times of pandemic. The article’s objective was to show the importance of financial inclusion to mitigate the effects of the COVID-19 crisis by inserting the population ―traditionally excluded― into the formal financial system. As a result of the research, it is shown that governments have mitigated the negative effects of the pandemic with the implementation of subsidy programs and by offering economic support to the vulnerable population; however, it is necessary to improve public policies to take advantage of digital innovation in benefit of the population, and to lower the barriers that hold back the penetration of financial inclusion.